PRINCIPLES OF SELECTING NOZZLES FOR OIL REFINERY REACTORS (American Journal of Business Management, Economics and Banking, 2024)
The article examines the issues of new ways to increase the efficiency of technological processes and improve the internal devices of reactors, the location of nozzles on the surface of the plate, gas flow rates, the cross-section of the nozzle with a flat diffuser.